(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Worldwide panic has been caused by the rapid spread of novel COVID-19 infection followed by millions of deaths and subsequently health threatening to the billions of human beings. Fast screening and isolation of the infected patients from the rest of the healthy population presented a great challenge to the health system.